Phylogeny and activity of proteobacteria in sediments from Lake Furnas - Martins, Gilberto (2011)
Sediments are sites of intense bacterial activity fostered by the presence of several organic and inorganic electron donors and acceptors that can be metabolised under either aerobic or anaerobic conditions. Among the bacterial groups populating sediments, the Proteobacteria phylum is one of the most abundant. Thus, the aim of the present work was to evaluate the contribution of Proteobacteria to nutrient (N and P) and iron cycling in sediments from the Azorean Lake Furnas (Portugal). The combination of denaturing gradient gel electrophoresis and cloning of the bacterial 16S rRNA gene fragment identified the Proteobacteria phylum as a dominant member of the sediment bacterial community from Lake Furnas. Using quantitative PCR to determine the relative amount of sediment bacteria affiliated to specific groups of Proteobacteria, it was inferred that 4.6% to 7.3% belonged to ammonium-oxidizing bacteria of the Beta-Proteobacteria phylum, Nitrobacter-like nitrite-oxidizing bacteria of the Alpha-Proteobacteria phylum amounted to 0.3% to 6.0%, Geobacteraceae-like iron reducing bacteria of the Delta-Proteobacteria phylum amounted to 1.0% to 2.4%, and Rhodocyclus-like phosphorus accumulating organisms of the Beta-Proteobacteria phylum accounted for 0.2% to 0.5%. Experiments with homogenized sediments in batch conditions indicated that bacteria performing autotrophic nitrification, heterotrophic denitrification, iron-reduction, and biological phosphorus storage/release were active in sediments from Lake Furnas. Lake Furnas is an advanced stage of eutrophication despite the considerable efforts that in the last decades have been made by local authorities towards the reduction of phosphorus inputs to the lake. Conventional remediation measures focused on the amount of P adsorbed into iron oxides that are released to the water column under anoxic conditions. The present work suggested that biological P storage/release by denitrifying bacteria in sediments might as well contribute to the release of phosphorus from sediments. Future measures towards lake restoration should include in addition to the classical procedure an evaluation of the contribution of biological processes in sediments to the eutrophication problem.